Nepal’s Economic Growth in the Context of Absorption, Trade Imbalance and the Fixed Exchange Rate - Basyal, Tula Raj (Banking Journal, 2011)
DOI: http://dx.doi.org/10.3126/bj.v1i1.5138 Banking Journal Vol.1(1) 2011: 1-12